مستوي تمكن طلاب جامعة الإمام محمد بن سعود الإسلامية من مهارات تلخيص النصوص العلمية - الأخشمي، أحمد بن علي بن أحمد (جامعة عين شمس - كلية التربية - الجمعية المصرية للمناهج وطرق التدريس, 2016)
هدفت الدراسة إلى تحديد مهارات تلخيص النصوص العلمية اللازمة لطلاب المرحلة الجامعية، ثم الكشف عن مستوى تمكن طلاب جامعة الإمام محمد بن سعود الإسلامية من تلك المهارات، بالإضافة إلى تعرّف الفروق ذات الدلالة الإحصائية – إن وجدت – في مستوى التمكن من تلك المهارات بناء على اختلاف نوع الكلية. ولتحقيق أهداف الدراسة استخدم الباحث المنهج الوصفي، وقام بتصميم اداتين للدراسة بالطريقة العلمية، هما: قائمة مهارات التلخيص، واختبار التلخيص. وطبق الاختبار على طلاب جامعة الإمام محمد بن سعود الإسلامية المسجلين في مقرر ( المناهج وطرق التدريس) في كليات: الشريعة، وأصول الدين، واللغة العربية، والعلوم الاجتماعية، والأعلام والاتصال، واللغات والترجمة. وقام الباحث باختيار عينة عشوائية من تلخيصات الطلاب بنسبة (25%) من كل كلية؛ ليقوم بتصحيحها وفق المقياس المعد لهذا الغرض، وفي ضوء ذلك بلغت عينة الدراسة (246) طالبا. وتوصلت الدراسة للنتائج الآتية: 1. الخروج بقائمة مكونة من (13) مهارة لازمة لطلاب المرحلة الجامعية لتلخيص النصوص العلمية. 2. أن مستوي تمكن طلاب جامعة الإمام محمد بن سعود الإسلامية من مهارات تلخيص النصوص العلمية كان متوسطا، حيث بلغ المتوسط العام لدرجات الطلاب (1.32) من (2.00) 3. وجود فروق ذات دلالة إحصائية عند مستوي دلالة (0.05) بين أفراد عينة الدراسة من طلاب كلية أصول الدين وطلاب كليات، والشريعة، والعلوم الاجتماعية، والأعلام والاتصال، واللغة العربية، لصالح طلاب كليات الشريعة، والعلوم الاجتماعية، والأعلام والاتصال، واللغة العربية. وفي ضوء هذه النتائج أوصت الدراسة بعدد من التوصيات، واقترحت عددا من الدراسات العلمية.
This study aimed to determine the summarizing skills of academic textsrequired for universitystagestudents, then demonstrating the abilitylevel of summarizing skills for Imam Mohamed Ibn Saud Islamic University students; in addition to recognizingthe statistically significant differences-if any- in the abilitylevel of Summarizing skills, taking into account the differences of college’s types. The researcher used the descriptive approach to achieve the objectives of this study; he also developed two study tools (questionnaires) in scientific method as follows: summarizing skills list, and summarizing test. The test was applied tolmam Mohamed Ibn Saud Islamic University students enrolled in course of Curriculum and Instruction, in Colleges of Sharia, Fundamentals of Religion, Arabic Language, social Sciences, Information and communication,and Languages and Translation. The researcher has chosen a random sample of students’ summaries representing (25%) of every college, for correcting these samples according to the standard provides for such a purpose. In light of the above mentioned, the study sample readied (246) students. The study results has indicated the foaowing: 1. Coming up with a list composed of (13) skills required for university stage students for summarizing academic texts. 2. Abilitylevel of summarizing skills for Imam Mohamed Ibn Saud Islamic University studentswas Mid-level, in terms that the students' GPA has reached (1.32) from (2.00). 3. The results showed that there are statistically significant differences at the level of (0.05)between the study samplestudents of Fundamentals of Religion College, and students ofSharia, Social Sciences, Information and communication, and Arabic Language colleges, in favor of students of Sharia, Social Sciences, Information and communication, and Arabic language colleges. In light of these results the researcher recommended a number of recommendations, and suggested a number of scientific studies.
Keywords: طلاب الجامعة -- مهارات التلخيص -- جامعة الإمام محمد بن سعود الإسلامية -- النصوص العلمية